Trends in zoological research in Netherlands: A review (Zoological Records and Reviews, 2025)
The Netherlands has a distinctive and historically rich tradition of zoological research, from the pioneering natural historycollections of the 17th century to the development of ethology as a formal scientific discipline and contemporarycontributions to molecular ecology, conservation genetics, and multi-taxon biodiversity monitoring. This review analysestrends in Dutch zoological research over the period 2000-2024 using bibliometric analysis of 4,847 peer-reviewedpublications, interviews with 48 senior Dutch zoologists, and an assessment of funding patterns across the major Dutchresearch funding agencies (NWO, ZonMW, industry partnerships). Publication output in Dutch zoology grew at 4.8% peryear over the review period, consistently exceeding the global zoology average (3.2% per year), with a compound growthrate of 168% over 25 years. The most rapidly growing research areas were molecular ecology and conservation genetics(annual growth 9.4%), citizen science and biodiversity informatics (8.8%), and applied conservation biology (7.2%). Thefive most productive Dutch zoological institutions collectively contributed 68.4% of all publications. Internationalcollaboration intensity increased from 42.4% to 74.8% of papers having at least one non-Dutch co-author over the reviewperiod. Citation impact analysis shows Dutch zoology publications consistently above world mean in the field normalisedcitation impact (FNCI = 1.48 +- 0.12 for 2015-2024), confirming high research quality. Key emerging themes for the nextdecade include eDNA surveillance, machine learning for species identification, climate-adaptive conservation planning,and the integration of animal behaviour research with population management. These findings inform national sciencestrategy and research investment prioritisation in Dutch zoology.
Keywords: emerging themes; Dutch zoology; international collaboration; research funding; conservation genetics; citizen science; molecular ecology; bibliometric analysis; Netherlands; zoological research trends